COMPARATIVE LITERATUREOF NOVEL SURAT KECIL UNTUK TUHANAND OSCARAND THE LADY IN PINK - Noryunita, Andri; Purwatiningsih, Dewi (Universitas Negeri Surabaya, 2015)
Comparative study is the way to make comparison of two (possibly more) things. In literature, there are some aspects that could be compared such as the literary work itself. This study discusses about two literary works from different culture and different author. The first one is novel which title Surat Kecil Untuk Tuhan by Agnes Devauner and the second is short story from Eric-Emmanuel Schmitt which title Oscar and the Lady in Pink. The purpose of this study is to compare about the intrinsic elements of both literary works and to compare about the main character there. The method which is used to this study is qualitative research because of the data collected by the word or sentence but not the number. Qualitative data deals with descriptions which could be observed and not measured. The results of this study showed to the reader about the intrinsic elements of both different literary works and also the comparison between the main characters of each literary work. Hopefully this study will give the beneficial to the reader in terms of comparative study.